1982
DOI: 10.1037/0033-295x.89.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm and timing in skill.

Abstract: The concept of rhythm points to diverse phenomena in skilled performance. A theoretical frame sufficiently general to deal with these is presented, together with data from a variety of skills. It is argued that a motor system, responsible for movement production, can produce movements that realize given time-scales and hence can act as a timekeeper. In contexts requiring temporal coordination, a more abstract timekeeper, or clock, can provide temporal references for a motor system or several motor subsystems; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
5

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 42 publications
4
69
1
5
Order By: Relevance
“….' This type of example suggests that timing variability is different at target attainment versus movement onset, difficult to explain in mass-spring models such as AP/TD, but easier to explain in extrinsic timing models because they can allow separate timing specification and prioritization for target attainment versus other parts of movement [100]. Several studies have confirmed the finding of differential variability in the timing of target attainment, compared with the timing of other movement events such as movement onset ( [91,[101][102][103][104], for non-speech motor activity; [105] for speech).…”
Section: (C) Evidence For Extrinsic Timingmentioning
confidence: 99%
“….' This type of example suggests that timing variability is different at target attainment versus movement onset, difficult to explain in mass-spring models such as AP/TD, but easier to explain in extrinsic timing models because they can allow separate timing specification and prioritization for target attainment versus other parts of movement [100]. Several studies have confirmed the finding of differential variability in the timing of target attainment, compared with the timing of other movement events such as movement onset ( [91,[101][102][103][104], for non-speech motor activity; [105] for speech).…”
Section: (C) Evidence For Extrinsic Timingmentioning
confidence: 99%
“…There is evidence for preferred, simple time ratios in produced rhythms (Essens, 1986;Fraisse, 1956Fraisse, , 1964Fraisse, , 1982Povel, 1981;. Furthermore, skilled musicihns often accurately produce higher order time spans and complex rhythmic ratios ~° (Clarke, 1985a(Clarke, , 1985bShaffer, 1981Shaffer, , 1982. We claim that many deviations that do occur are most reasonably represented as additive time changes that arise either from a performer's (a) failure to capture difficult ratio notations and/or (b) conscious attempts to communicate rhythmic style (e.g., legato, staccato) or emotion via tempo change (Clarke, 1984;Gabrielsson, 1974;Gabrielsson, Bengtsson, & Gabrielsson, 1983; Shalfer, Clarke, & Todd, 1985).…”
Section: Rhythm Refers To Patterned Time Changes Within a Metricmentioning
confidence: 99%
“…In hierarchical theories of motor control (MacKay, 1982(MacKay, , 1989Shaffer, 1980Shaffer, , 1982 and theories of mental practice (Feltz & Landers, 1983;Feltz, Landers, & Becker, 1988), it is speculated that the two types of performance share the higher, cognitive levels of the hierarchy but differ in terms of the level at which performance output occurs. In experiments assessing practice and transfer effects for speech production, MacKay (1981) demonstrated that there are similarities between mental and physical practice and that mental execution times reflect internal processing.…”
mentioning
confidence: 99%